2023
DOI: 10.1002/ps.7503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of entomopathogenic fungi, nematodes and spinetoram combinations for integrated management ofThrips tabaci

Abstract: BACKGROUND: Two consecutive field trials using a blend of entomopathogens in combination with a new chemistry insecticide were conducted to determine treatment effects on onion thrips (Thrips tabaci Lindeman) populations, crop damage, plant development, crop yield and impact on natural enemies. Products were tested in an onion cropping system and included the insect pathogenic fungus Beauveria bassiana (isolate WG-11), an entomopathogenic nematode Heterorhabditis bacteriophora (strain VS) and the new-chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Rizwan et al found that B. bassiana and diatomaceous earth (DE) are more effective in combination against Tribolium castaneum on wheat, which is due to the ability of DE to destroy the insect cuticle [ 135 , 136 ]. Wakil et al demonstrated that simultaneous use of B. bassiana and the chemical insecticide spinetoram significantly reduced onion thrip larvae and adults and increased onion production [ 137 ].…”
Section: Problems and Development Trend Of Mycopesticidesmentioning
confidence: 99%
“…Rizwan et al found that B. bassiana and diatomaceous earth (DE) are more effective in combination against Tribolium castaneum on wheat, which is due to the ability of DE to destroy the insect cuticle [ 135 , 136 ]. Wakil et al demonstrated that simultaneous use of B. bassiana and the chemical insecticide spinetoram significantly reduced onion thrip larvae and adults and increased onion production [ 137 ].…”
Section: Problems and Development Trend Of Mycopesticidesmentioning
confidence: 99%
“…Numerous efforts have been made to develop biological control agents (BCAs) as alternatives or supplements to these chemicals. These include the utilization of microbial control agents against insect pests, such as bacteria, viruses and fungi [4][5][6][7][8][9][10]. In 2022, at the Annual Biocontrol Industry Meeting (ABIM) held in Basel, Switzerland, Marrone provided an update on the share of the biological market [11].…”
Section: Introductionmentioning
confidence: 99%